Five new species of Baeus Haliday, 1833 (Hymenoptera: Platygastroidea: Scelioninae) from Brazil with an updated key to Neotropical species - Araujo, Rodrigo De Oliveira; Vivallo, Felipe; Araujo, Cristina De Oliveira (Zootaxa, 2013)
The species of the genus Baeus are small endoparasitoids wasps that attack spiders’ egg sacs. Although there are data of occurrence in several biogeographical regions, their distribution records are scarce, especially due to their small size, mak-ing difficult to collect them in natural environments. In this paper, five new species of Baeus are described as results of collections made in southeastern Brazil: Baeus fluminensis new species, B. itatiaiaensis new species, B. leucophthalmus new species, B. melanocephalus new species and B. morenus new species. An updated key to the known Neotropical spe-cies of the genus is also provided.